Differences in estimation of sugarcane phenotypic parameters using unmanned aerial vehicle multispectral and hyperspectral data - Chen Yanli; Huang Lu; Yang Shaoe; Sun Ming; Ding Meihua; Huang Lining; Ma Ruisheng; Liang Chi; Yang Xin; Chen Cheng (Computers and Electronics in Agriculture, 2026)

A single cyano-borate additive for decoupled cathode–anode crosstalk and 4.7 V LiCoO2 batteries - Lining Pan; Junhua Zhao; Tiefeng Liu; Zhenjia Shi; Huicong Huang; Xiangjie Zhao; Tingzhou Yang; Ruo Wang (Chemical Engineering Journal, 2026)

Swimming Training Alters Immune Cell Spatiotemporal Distribution to Mitigate Fat Infiltration and Enhance Muscle Regeneration - Quanzhong Ren; Guihe Yang; Lining Xu; Dingding Wang; Wenkai Wu; Anyi Guo; Jianxun Guo; Ling Wang; Yajun Liu; Renxian Wang (Phenomics, 2026)

Multi-objective optimization for integrated energy systems using non-dominated sorting genetic and swarm intelligence methods - Feng Li; Yonghui Chen; Ying Hu; Yang Yu; Lining Xing (Swarm and Evolutionary Computation, 2026)

Novel remediation strategies for Cr(VI)-contaminated groundwater at low temperature: Study on the effects of combining ascorbic acid reduction with biostimulation - Xinru Yang; Lining Hou; Xiang Yuan; Haijuan Guo; Fang Ma (Journal of Environmental Management, 2026)

Sugarcane Phenotypic Parameters Modeling Using Unmanned Aerial Vehicle Multispectral Data - Yanli Chen; Lu Huang; Mingzhi Li; Ming Sun; Meihua Ding; Lining Huang; Ruisheng Ma; Chi Liang; Xin Yang; Cheng Chen (Sugar Tech, 2026)

Preparation and characterization of gelatin/bacterial nanofibrillated cellulose composite membranes based on an ecological engineering strategy - Fengge Yu; Jieying Fan; Jialin Zhang; Xiangying Liu; Yue Meng; Yanping Chi; Zhiqiang Yang; Caiming Li; Hongrui Sun; Hua Zhang; Lining Kang (Food Hydrocolloids, 2026)

Interfacial solar-driven seawater desalination: From material innovations to system integration and future perspectives - Nana Wang; Yanfeng Yang; Lining Zhang; Pinqi Feng; Xiangshan Bi; Cun Zhou (Desalination, 2026)

Magmatic plumbing systems of the Tarim Large Igneous Province as revealed by 3D seismic images - Shenghan Zhang; Wenbin Zhu; Bohua Zhu; Nijiati Aibibula; Lining Yang; Nan Wu; Jiangfeng Yang (Tectonophysics, 2026)

The application of magnetic therapy in stroke treatment: Traditional treatment and biomaterials - Yi Fan; Xinyu Zhang; Lei Zhang; Xiaoyu Han; Haitong Zhao; YuJie Zhong; Xuan Jiang; Yutian Wei; Yan Pi; Yunyan Wang; Xinyi Yao; Yuge Ye; et al. (Chemical Engineering Journal, 2026)

Investigation of Turbulence Intensity Effects on Tidal Turbine Wakes Through the BEM–CFD Method - Erhu Hou; Yang Li; Lining Zhu; Yanan Wu; Jie Ding; He Wu (Journal of Marine Science and Engineering, 2025)
The wake characteristics of tidal turbines are significantly influenced by turbulence intensity (TI) and flow velocity in the marine environment. This study employs the Blade Element Momentum (BEM)–CFD method to model two-bladed horizontal tidal turbine wakes, simplifying the turbine geometry while ensuring computational efficiency. The numerical model, validated against experimental data, demonstrates reliable accuracy. Simulations were conducted for background TI levels of 2%, 6%, 10%, 14%, and 18%. Results indicate that wake regions initially expand and then contract, with the contraction point moving closer to the turbine as TI increases. At 2% TI, the wake influence region extends to an axial distance/diameter (X/D) ratio of 20, while at 18% TI, contraction begins at X/D = 4. Low TI results in more extensive low-speed regions, whereas high TI accelerates wake recovery. As TI increases, the wake’s turbulence rapidly blends with the background, leading to a reduction in turbulence increments within the wake. Additionally, an analytical wake model for tidal turbines was developed, incorporating turbulence intensity into the formula. The predicted curve exhibited good agreement with the CFD data. This model enables a quick and efficient prediction of wake velocity changes under varying turbulence intensities.

Reversible conversion superwetting coatings with TiO2-based heterojunction materials for enhancing efficient oily water treatment and water purification - Zhong Lv; Yanfeng Yang; Lining Zhang; Pinqi Feng; Xiaolu Zhai; Cun Zhou (Journal of Hazardous Materials, 2025)

Data-driven assisted multiobjective routing optimization for multimodal transportation under fuzzy demand - Jinlong Zhou; Yinggui Zhang; Juan Wang; Yang Xiao; Yuhan Wang; Xupeng Wen; Lining Xing (Swarm and Evolutionary Computation, 2025)

A consensus optimization mechanism with Q-learning-based distributed PSO for large-scale group decision-making - Qingyang Jia; Kewei Yang; Yajie Dou; Ziyi Chen; Nan Xiang; Lining Xing (Swarm and Evolutionary Computation, 2025)

Assessing the ecological effects of the World’s Largest Forestry Eco-engineering: Three-North Protective Forest Program within the initially scheduled range from 1978 to 2022 - Xiao Zheng; Jiaojun Zhu; G. Geoff Wang; Qiaoling Yan; Tao Sun; Lining Song; Tian Gao; Yirong Sun; Xiufen Li; Kai Yang; Jinxin Zhang; Lizhong Yu; et al. (Science China Life Sciences, 2025)

Development of a Csy4-Processing TRV-Based CRISPR/Cas9 Genome Editing System in Nicotiana benthamiana - Yanjie Luo; Xiaodong Tang; Cuihong Yu; Yang Qiu; Julia S. Nowak; Qing Shi Lu; Lining Tian; Ren Na (Plant Molecular Biology Reporter, 2024)
The CRISPR/Cas9 system is a site-specific genome editing tool that has been widely used in various plant species. The plant virus-based gRNA (guide RNA) delivery system, which differs from the typical Agrobacterium -mediated transformation, is an attractive method to facilitate the application of CRISPR/Cas9. The virally delivered gRNA is usually driven by heterologous plant U6 or viral promoters (e.g., pea early-browning virus, PEBV; barley stripe mosaic virus, BSMV). However, heterologous promoters may have poor performance in some cases. In this paper, a feasible option to detach gRNA(s) from the virus genome is employed. Specifically, the Csy4-RNA processing system is used to release gRNA(s) from the tobacco rattle virus (TRV). The coding sequences of Cas9 and Csy4 nucleases are cloned into a single polycistronic expression cassette under an estrogen-inducible promoter in a binary vector, and the gRNA is cloned into the TRV genome flanked by two 20 bp Csy4 recognition sites. The results show that the Csy4-processing TRV-based delivery system works effectively in targeting single and multiple sites, nucleotide replacement, and large fragment deletion in Cas9-mediated genome editing via transient expression in Nicotiana benthamiana . The Csy4-TRV is a promising gRNA(s) processing and delivery system for CRISPR/Cas9 genome editing. This method can be easily adapted to other plant RNA viruses, facilitating the application of the CRISPR/Cas9 system in plants.

Dynamic variable analysis guided adaptive evolutionary multi-objective scheduling for large-scale workflows in cloud computing - Yangkun Xia; Xinran Luo; Wei Yang; Ting Jin; Jun Li; Lining Xing; Lijun Pan (Swarm and Evolutionary Computation, 2024)

A novel fault detection and identification method for complex chemical processes based on OSCAE and CNN - Shangbo Han; Lining Yang; Dawei Duan; Longchao Yao; Kai Gao; Qingyuan Zhang; Yanwen Xiao; Weihong Wu; Jian Yang; Weijie Liu; Xiang Gao (Process Safety and Environmental Protection, 2024)

Ship Detection in Synthetic Aperture Radar Images Based on BiLevel Spatial Attention and Deep Poly Kernel Network - Siyuan Tian; Guodong Jin; Jing Gao; Lining Tan; Yuanliang Xue; Yang Li; Yantong Liu (Journal of Marine Science and Engineering, 2024)
Synthetic aperture radar (SAR) is a technique widely used in the field of ship detection. However, due to the high ship density, fore-ground-background imbalance, and varying target sizes, achieving lightweight and high-precision multiscale ship object detection remains a significant challenge. In response to these challenges, this research presents YOLO-MSD, a multiscale SAR ship detection method. Firstly, we propose a Deep Poly Kernel Backbone Network (DPK-Net) that utilizes the Optimized Convolution (OC) Module to reduce data redundancy and the Poly Kernel (PK) Module to improve the feature extraction capability and scale adaptability. Secondly, we design a BiLevel Spatial Attention Module (BSAM), which consists of the BiLevel Routing Attention (BRA) and the Spatial Attention Module. The BRA is first utilized to capture global information. Then, the Spatial Attention Module is used to improve the network’s ability to localize the target and capture high-quality detailed information. Finally, we adopt a Powerful-IoU (P-IoU) loss function, which can adjust to the ship size adaptively, effectively guiding the anchor box to achieve faster and more accurate detection. Using HRSID and SSDD as experimental datasets, mAP of 90.2% and 98.8% are achieved, respectively, outperforming the baseline by 5.9% and 6.2% with a model size of 12.3 M. Furthermore, the network exhibits excellent performance across various ship scales.

Northward expansion of the West Kunlun orogenic belt during the Cenozoic and its implications for the evolution of the northwest Tibetan Plateau: Constraints from sediment dispersal patterns in the Buya Basin, China - Shujun Liang; Xiubin Lin; Chunyang Li; Xiaochun Wei; Yang Qu; Kaixuan An; Cai Chen; Xianzhang Yang; Yong Li; Liang Zhang; Jiangwei Shang; Li Li; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Compositing of Co3O4 with boron nitride to promote the catalytic performance for methane oxidation - Haojie Wu; Xin Sui; Yang Lei; Lining Liu; Wenfan Xu; Gemeng Liang; Cuiqing Li; Xingyun Li (Fuel, 2024)

Microfluidic device featuring micro-constrained channels for multi-parametric assessment of cellular biomechanics and high-precision mechanical phenotyping of gastric cells - Yang Heng; Xinyu Zheng; Youyuan Xu; Jiaqi Yan; Ying Li; Lining Sun; Hao Yang (Analytica Chimica Acta, 2024)

Effects of thermal exposure to disposable plastic tableware on human gut microbiota and metabolites: A quasi-experimental study - Xue Zhang; Xiaoxue He; Degong Pan; Liping Shi; Yueping Wu; Yue Yang; Yongbin Zhu; Yanrong Wang; Huihui Wang; Lining Pu; Shulan He; Lingchen Meng; et al. (Journal of Hazardous Materials, 2024)

Long-lived Cenozoic positive relief of the south-Eastern Tian Shan: Insights from provenance analyses of the northwestern Kuqa Depression sediments - Jialun Huang; Xiubin Lin; Kaixuan An; Hanlin Chen; Xiaogan Cheng; Yang Qu; Yong Li; Xianzhang Yang; Liang Zhang; Cai Chen; Zhuxin Chen; Lin Jiang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

The Prevention Effect of Lactobacillus plantarum 17–5 on Escherichia coli-Induced Mastitis in Mice - Ke Li; Ming Yang; Li Jia; Mengyue Tian; Jinliang Du; Yinghao Wu; Lining Yuan; Lianmin Li; Yuzhong Ma (Probiotics and Antimicrobial Proteins, 2023)

Extracting static elastic moduli of rock through elastic wave velocities - Yuliang Zhang; Yiming Gu; Hongtu Zhou; Lining Yang (Acta Geophysica, 2023)
In many geological conditions, obtaining the static elastic moduli of crustal rocks is an essential subject for accurate mechanical analyses of crust. The elastic wave method may be the best choice if rock specimens cannot be taken since elastic wave propagation can be applied to in-situ environments. Although many signs of progress have been made in the elastic wave method, some issues still restrict the accurate extraction of static moduli and its applications. A review of this method and its further research prospect is urgently needed. With this purpose, this paper summarized and analyzed the published experimental data about the relationship between the static and dynamic Young’s moduli of rock, and the frequency dependence of wave velocities and dynamic elastic moduli. P- and S-wave velocities, Young’s, and bulk moduli of rock, especially the saturated rock, have strong frequency dependence in a wide frequency range of 10 –6 –10 6 Hz. Different rocks or conditions (such as water content, amplitude, and pressure), have different frequency-dependent characteristics. The current elastic wave method can be classified into two methods: the empirical correlation method and the multifrequency ultrasonic method. The basic principle, advantages, and disadvantages of both methods are analyzed. Especially, the reasonability of the multifrequency ultrasonic method was elaborated given the nonlinear elasticity, strain level/rate, and pores/cracks in rock materials. Existing problems and prospects on the two methods are also pointed out, such as the choice of a proper empirical correlation, accurate determination of the critical P- and S-wave velocities, the prediction of Young’s modulus at each strain level, and the reasonability of the method under various water contents and fracture structures.

How did the Tonga volcanic tsunami on January 15, 2022, affect Chinese coasts? - Zongchen Wang; Zhiguo Xu; Ye Yuan; Huaiwei Yang; Lining Sun; Peitao Wang; Tingting Fan (Science China Earth Sciences, 2023)

Improved ant colony optimization for the vehicle routing problem with split pickup and split delivery - Teng Ren; Tianyu Luo; Binbin Jia; Bihao Yang; Ling Wang; Lining Xing (Swarm and Evolutionary Computation, 2023)

RL-GA: A Reinforcement Learning-based Genetic Algorithm for Electromagnetic Detection Satellite Scheduling Problem - Yanjie Song; Luona Wei; Qing Yang; Jian Wu; Lining Xing; Yingwu Chen (Swarm and Evolutionary Computation, 2023)

Exploring the driving factors of haze events in Beijing during Chinese New Year holidays in 2020 and 2021 under the influence of COVID-19 pandemic - Lining Luo; Xiaoxuan Bai; Yunqian Lv; Shuhan Liu; Zhihui Guo; Wei Liu; Yan Hao; Yujiao Sun; Jiming Hao; Kai Zhang; Hongyan Zhao; Shumin Lin; et al. (Science of The Total Environment, 2023)

Understanding and revealing the intrinsic impacts of the COVID-19 lockdown on air quality and public health in North China using machine learning - Yunqian Lv; Hezhong Tian; Lining Luo; Shuhan Liu; Xiaoxuan Bai; Hongyan Zhao; Kai Zhang; Shumin Lin; Shuang Zhao; Zhihui Guo; Yifei Xiao; Junqi Yang (Science of The Total Environment, 2023)

Efficient oil-water emulsion treatment via novel composite membranes fabricated by CaCO3-based biomineralization and TA-Ti(IV) coating strategy - Hongli Xie; Binghong Chen; Hongjun Lin; Renjie Li; Liguo Shen; Genying Yu; Lining Yang (Science of The Total Environment, 2023)

Revisiting the Evaluation of Hydraulic Transmissivity of Elliptical Rock Fractures in Triaxial Shear-Flow Experiments - Yinlin Ji; Hannes Hofmann; Ernest H. Rutter; Fei Xiao; Lining Yang (Rock Mechanics and Rock Engineering, 2022)
Highlights • A novel numerical approach has been proposed to retrieve the hydraulic transmissivity of elliptical rock fractures in triaxial shear-flow experiments. • The accuracy of different methods for estimation of hydraulic transmissivity of elliptical rock fractures has been evaluated and discussed. • The numerical approach and electrical analogy are recommended for accurate evaluation of hydraulic transmissivity of elliptical rock fractures.

Peripheral blood and urine metabolites and biological functions in post-stroke depression - Haiyan Liu; Juncai Pu; Qinxiang Zhou; Lining Yang; Dingqun Bai (Metabolic Brain Disease, 2022)

Analysis of the influence of the multi-fracture water flow and heat transfer direction on the near-field temperature of high-level radioactive waste repository - Junyi Gao; Yonggang Zhang; Qipeng Shi; Lining Yang (Arabian Journal of Geosciences, 2021)

Predicting the presence and mechanism of busulfan drug-drug interactions in hematopoietic stem cell transplantation using pharmacokinetic interaction network–based molecular structure similarity and network pharmacology - Chenxia Hao; Xiaoqin Ma; Lining Wang; Weixia Zhang; Jiong Hu; Jingjing Huang; Wanhua Yang (European Journal of Clinical Pharmacology, 2021)

A novel dynamic predictive method of water inrush from coal floor based on gated recurrent unit model - Yonggang Zhang; Lining Yang (Natural Hazards, 2021)

Experimental investigation of reactions between two-mica granite and boron-rich fluids: Implications for the formation of tourmaline granite - Lining Cheng; Chao Zhang; Xiaosong Yang; Dongmei Qi; Yongsheng Zhou; Francois Holtz (Science China Earth Sciences, 2019)

Laboratory-based geoelectric monitoring of water infiltration in consolidated ground - Lining Yang; Qiang Sun; Haiping Yang (Hydrogeology Journal, 2018)

Variations of Strength, Resistivity and Thermal Parameters of Clay after High Temperature Treatment - Qiang Sun; Weiqiang Zhang; Yuliang Zhang; Lining Yang (Acta Geophysica, 2016)

Perceived reputation of others modulates empathic neural responses - Li Zheng; Qianfeng Wang; Xuemei Cheng; Lin Li; Guang Yang; Lining Sun; Xiaoli Ling; Xiuyan Guo (Experimental Brain Research, 2016)

The Expression of Calcitonin Gene-Related Peptide and Acetylcholine in the Vestibular-Related Nucleus Population of Wild-Type Mice and Retinal Degeneration Fast Mice After Rotary Stimulation - Wang Xiaocheng; Shi Zhaohui; Bian Ka; Xue Junhui; Zhang Lei; Xia Feng; Yang Guoqing; Feng Lining; Zhang Zuoming (Journal of Molecular Neuroscience, 2013)

Zinc Inhibits High Glucose-Induced Apoptosis in Peritoneal Mesothelial Cells - Xiuli Zhang; Dan Liang; Baolei Guo; Lina Yang; Lining Wang; Jianfei Ma (Biological Trace Element Research, 2012)

Zinc Supplementation Attenuates High Glucose-Induced Epithelial-to-Mesenchymal Transition of Peritoneal Mesothelial Cells - Xiuli Zhang; Jun Wang; Yi Fan; Lina Yang; Lining Wang; Jianfei Ma (Biological Trace Element Research, 2012)

STAT1 mediates cellular senescence induced by angiotensin II and H2O2 in human glomerular mesangial cells - Sumin Jiao; Fanji Meng; Jin Zhang; Xue Yang; Xiaoyu Zheng; Lining Wang (Molecular and Cellular Biochemistry, 2012)

Arabidopsis ERF4 is a transcriptional repressor capable of modulating ethylene and abscisic acid responses - Zhen Yang; Lining Tian; Marysia Latoszek-Green; Daniel Brown; Keqiang Wu (Plant Molecular Biology, 2005)